2021
DOI: 10.1093/jac/dkab447
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of Cas13a-based diagnostic assay forNeisseria gonorrhoeaedetection and azithromycin resistance identification

Abstract: Background Gonorrhoea, caused by Neisseria gonorrhoeae, has spread worldwide. Strains resistant to most antibiotics, including ceftriaxone and azithromycin, have emerged to an alarming level. Rapid testing for N. gonorrhoeae and its antimicrobial resistance will therefore contribute to clinical decision making for early diagnosis and rational drug use. Methods A Cas13a-based assay (specific high-sensitivity enzymatic reporter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In these studies, gold nanoparticles were used as the colorimetric probe. Luo et al reported a similar detection limit of 10 copies µL −1 for a Cas13a-based specific high-sensitivity enzymatic reporter unlocking (SHERLOCK) assay developed for NG porA and azithromycin resistance detection [ 38 ]. It may be noted that this assay was tested on only purified double-stranded DNA (dsDNA).…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, gold nanoparticles were used as the colorimetric probe. Luo et al reported a similar detection limit of 10 copies µL −1 for a Cas13a-based specific high-sensitivity enzymatic reporter unlocking (SHERLOCK) assay developed for NG porA and azithromycin resistance detection [ 38 ]. It may be noted that this assay was tested on only purified double-stranded DNA (dsDNA).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Yersinia pestis , the main pathogen causing plague, was detected by the RPA-SHERLOCK method with an LOD of as low as 700 zM (420 copies/ml; Schultzhaus et al, 2021 ). Using the RPA-SHERLOCK assay, Luo et al (2021) detected 10 copies/μl of the porA gene of Neisseria gonorrhoeae and successfully identified two azithromycin resistance mutations.…”
Section: Cas13a-based Detection Of Bacteria and Other Pathogensmentioning
confidence: 99%
“…Cas13a-based detection methods could recognize SNP in target gene via artificially adding mismatch between crRNA and target RNA, exhibiting the potential to detect AMR mutants. Following to this mechanism, several studies have achieved detection of AMR mutants in different pathogens ( Kiga et al, 2020 ; Cunningham et al, 2021 ; Luo et al, 2021 ; Bai et al, 2022 ). Cunningham et al demonstrated the capability of RPA-SHERLOCK assay for recognizing the A581G mutant in P. falciparum associated with sulfadoxine resistance ( Cunningham et al, 2021 ).…”
Section: Cas13a-based Detection Of Bacteria and Other Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel point-of-care diagnostics for N. gonorrhoeae are increasingly available. 18,19 20 Further, some of those tests appear to be both feasible and acceptable in low-resource settings. 21 However, few have met the World Health Organization (WHO) standards for point-of-care tests: real-time connectivity, ease of specimen collection, affordable, sensitive, specific, user-friendly, rapid and robust, equipment free/environmentally friendly, deliverable to end-users.…”
Section: Introductionmentioning
confidence: 99%